Our "Event-Full" World... the Challenge to an Anthropologist - Paine, Robert (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1995)
This article makes a case for "event anthropology" in today’s world. "Event" is distinguished from "happening" and the characteristics of the world in which anthropology is situated today are delineated; the essay then turns to illustrative case-histories in Norway and Israel. These highlight the increasing frequency of "under"-understood events and associated senses of powerlessness on the one hand, and on the other, the place of invention in the conditions of contemporary modernity - not just in response to events but also in their making. Attention is paid to the crumbling of group solidarity as an anthropological axiom.